Activation of the cognitive and informative process in teaching foreign students (pre-level preparation stage) - Sira, L.; Сіра, Лариса Іванівна (Osaka, Japan, 2020)
The article deals with the use of non-traditional forms of conducting classes that promote interest to the study of the subject, develop the creative independence of foreign students, get used to working with various sources. It is shown, on the example of studying the course "Ukrainian language", the expediency of using non-traditional forms of teaching as one of the methods of activating educational and cognitive activity.
Keywords: матеріали конференцій; unconventional forms; cognitive activity; playing lessons; intellectual game; debate